Annual Report on the List of actions to advance LGBTI Equality. (Brussel : European Commission, 2016)
Fonds Suzan Daniel (FSD)
Periodiciteit : jaarlijks
Redactie : Directorate General for Justice and Consumers
Engels
Periodiek